THE INFLUENCE OF KNOWLEDGE, TAXPAYER AWARENESS, AND TAX SANCTIONS ON TAX COMPLIANCE - Cathlin Amanda; Dudi Abdul Hadi (Jurnal Bisnis, Ekonomi, dan Sains, 2023)
The purpose of this research is to understand the overview of knowledge, taxpayer awareness, and tax sanctions on the compliance of MSME taxpayers in the city of Bandung. Additionally, it aims to determine the influence of knowledge, taxpayer awareness, and tax sanctions on the compliance of MSME taxpayers in Bandung, both simultaneously and partially. The method used in this research is quantitative descriptive method. The population in this study consists of MSME taxpayers registered at the Tegallega Primary Tax Office in Bandung. The sampling technique used in this research is convenience sampling. The research findings indicate that taxpayer knowledge and tax sanctions influence the compliance of MSME taxpayers, while taxpayer awareness does not affect the compliance of MSME taxpayers